The effects of coaching on individual outcomes: a mediation model by psychological capital - Fontes, A. (European Association of Work and Organizational Psychology (EAWOP), 2019)
✓ The effects of coaching on individual outcomes: a mediation model by psychological capital ✓ Purpose Coaching is a developmental intervention often implemented in organizations to improve individual attitudes and behaviors. However, few studies have empirically investigated these assumptions and even fewer looked at explaining mechanisms (Jones et al., 2016). We propose psychological capital (Psycap), a set of positive individual resources, as possible mediator. We intended to investigate whether: 1) coaching is effective in improving Psycap; 2) coaching impacts positively the individual outcomes; 3) Psycap works as mediator; 4) coaching effects maintain over time. ✓ Design/Methodology/Approach/Intervention We conducted an experiment with 56 employees in marketing company, who were either assigned to a coaching intervention or a wait-list control group. Before the program started (T1), Psycap and other measures (job attitudes and other-rated individual performance) were collected, being measured again (T2) after the coaching intervention that lasted 4 months. Four months later (T3), the same variables were measured for the experimental group. ✓ Results ANOVAs showed coaching was associated with increases in Psycap, job attitudes, and two dimension of performance. The mediating role of Psycap, analyzed with PROCESS (Hayes, 2016) was supported. The effects on Psycap and job attitudes lasted over time, as revealed by within-subjects repeated measures analyses. ✓ Limitations The sample size is relatively small and the data was collected only in one company. ✓ Research/Practical Implications This study fills a gap in our knowledge of the underlying mechanisms behind coaching effectiveness. ✓ Originality/Value This is one of the few experimental studies on coaching effectiveness that used a control group as well as a longitudinal design.